Cardiac toxicities of anticancer treatments: chemotherapy, targeted therapy and immunotherapy. (July 2019) - Zarifa, Abdulrazzak; Albittar, Aya; Kim, Peter Y.; Hassan, Saamir; Palaskas, Nicolas; Iliescu, Cezar; Durand, Jean-Bernard; Lopez-Mattei, Juan
Abstract : Purpose of review: Current oncologic treatments have shown improvement in overall survival in cancer patients. However, the cardiac toxicities of cancer therapeutics, particularly chemotherapy, targeted therapy and immunotherapy can have life-threatening side effects. Recent findings: A MEDLINE search for cardiovascular toxicities associated with Federal Drug Administration (FDA)-approved cancer treatments including chemotherapy, targeted therapy and immunotherapy was performed. We included comprehensive articles and research articles establishing the incidence, diagnosis, monitoring and management of cardiovascular toxicities related to cancer treatments until January 2019. This review highlights the mechanisms and epidemiology of cardiotoxicity associated with some cancer treatments. The most common cardiovascular side-effects are discussed at an introductory level with emphasis on those related with the development of heart failure. Summary: Cardiovascular side effects of cancer treatments are common and might affect the survival in cancer patients. Recognition and management of these side effects require understanding of their mechanisms and their clinical manifestations. A multidisciplinary approach with understanding of both the cardiovascular and oncologic risks is necessary in order to provide well tolerated and effective cardio-oncology care.